India becoming : a portrait of life in modern India - Akash Kapur (Riverhead Books, 2013)
"A portrait of incredible change and economic development, of social and national transformation told through individual lives. The son of an Indian father and an American mother, Akash Kapur spent his formative years in India and his early adulthood in the United States. In 2003, he returned to his birth country for good, eager to be part of its exciting growth and modernization. What he found was a nation even